The Effect of Mental Training That Accompanies Skill Learning to Learn Some of the Fundamental Skills in Boxing - Abbas, ElafRabeea (International Journal of Psychosocial Rehabilitation, 2020)
This research deals with the importance and role of mental training in giving positive results to educational and training processes and raising the technical level in the performance of skills for all sports, and indicates the importance of the research as mental training is not limited to its use in competitions but is used in the field of movement in general. It is very important in the stage of acquiring skills, so it was of very high importance and influencing the education and training processes. As for the research problem, the researcher touched on the neglect of this type of training by our teachers and trainers when developing their educational or training curricula due to the lack of information available to them about the basics of this training and the factors required to be. Available to work on it to make educational and training operations successful. Therefore, the hesitation and fear of possible negative effects has an already prepared curriculum, which is the reason for moving away from this important type of training, and thus the lack of an important work pillar to reach the curriculum objectives. The research aims to identify the effect of mental training on learning basic boxing skills, in addition to a comparison between the effect of mental training added to the training curriculum and the effect of the training curriculum on learning basic boxing skills. “Research Methodology and Field Procedures”: This chapter includes the methodology used by the researcher in the research, which is the experimental method, and a description of the research sample. The research procedures included preparing a curriculum for learning skills for boxing and another for mental training, presenting the two approaches to experts, each according to their specialization, Arabizing a questionnaire for athlete perception, and preparing a questionnaire to assess the skill performance of some. Basic skills in the game of boxing. Conducting the main experiment by applying the two approaches and conducting post-tests on the research sample. The researcher concluded by discussing the results, the researcher reached several conclusions that the goal had achieved, as his research showed that the method of training mental facilities for physical learning was effective, although the use of this type of training gives greater effectiveness in learning basic skills compared to teaching the gifted technically only, and based on these results it recommended The researcher made some recommendations. The study purpose: This study is aimed at knowing the effect of mental training that accompanies skill learning and comparing it with a skillful learning program to learn some of the Fundamental Skill of Boxing. The study results: Results indicated that there was no significant difference between the pre and posttest of imagination for the control group. There was a significant difference between the pre and posttest of imagination for the experimental group. There was a significant difference between the control and experimental groups in the skill test and favor of the second group too. These results emphasized the importance of the mental training that accompanies skill learning relative to skill learning alone